ANALISIS PENGARUH KUALITAS LINGKUNGAN FISIK, KUALITAS MAKANAN DAN KUALITAS LAYANAN TERHADAP MINAT BELI ULANG DAN MINAT WORD OF MOUTH (Studi Empiris pada Du Cafe Semarang) - Darwis Lantas Hutabarat; I Made Sukresna (Faculty of Economics and Business | Universitas Diponegoro, 2019)
This study aims to analyze the impact of physical environment quality, food quality, and service quality on the repurchasing interest and word of mouth interest in Du Cafe Semarang. The population in this thesis are the consumers of Du Cafe Semarang. The number of sample used is 200 selected persons, using purposive sampling method, while the data resource are mainly obtained from the questioners that was analyzed afterwards by AMOS program.The result of this study shows that physical environment do not affect toward consumers satisfaction, while food quality and service quality affect positively on consumers satisfaction. Moreover, consumers satisfaction have an positive impact on the interest in repurchasing and the interest in word of mouth. The Variable that affect interest in repurchasing and the interest in word of mouth the most in Du Cafe is service quality. Thus, the quality of service becomes a crucial determinant of a café strategy success.